Stromal Claudin14-heterozygosity, but not deletion, increases tumour blood leakage without affecting tumour growth. - Marianne Baker (Public Library of Science (PLoS), 2013)
The maintenance of endothelial cell-cell junctions is vital for the control of blood vessel leakage and is known to be important in the growth and maturation of new blood vessels during angiogenesis. Here we have investigated the role of a tight junction molecule, Claudin 14, in tumour blood vessel leakage, angiogenesis and tumour growth. Using syngeneic tumour models our results showed that genetic ablation of Claudin 14 was not sufficient to affect tumour blood vessel morphology or function. However, and surprisingly, Claudin 14-heterozygous mice displayed several blood vessel-related phenotypes including: disruption of ZO-1-positive cell-cell junctions in tumour blood vessels; abnormal distribution of basement membrane laminin around tumour blood vessels; increased intratumoural leakage and decreased intratumoural hypoxia. Additionally, although total numbers of tumour blood vessels were increased in Claudin 14-heterozygous mice, and in VEGF-stimulated angiogenesis ex vivo, the number of lumenated vessels was not changed between genotypes and this correlated with no difference in syngeneic tumour growth between wild-type, Claudin 14-heterozygous and Claudin 14-null mice. Lastly, Claudin 14-heterozygosity, but not complete deficiency, also enhanced endothelial cell proliferation significantly. These data establish a new role for Claudin 14 in the regulation of tumour blood vessel integrity and angiogenesis that is evident only after the partial loss of this molecule in Claudin 14-heterozyous mice but not in Claudin 14-null mice.